Erythrocyte caspase-3 activation and oxidative imbalance in erythrocytes and in plasma of type 2 diabetic patients - Maellaro, Emilia; Leoncini, Silvia; Moretti, Daniele; Del Bello, Barbara; Tanganelli, Italo; De Felice, Claudio; Ciccoli, Lucia (Acta diabetologica, 2013)
An increased oxidative stress and a decreased life span of erythrocytes (RBCs) are reported in patients with diabetes. Aim of this study was to assess in RBCs from patients with type 2 diabetes whether downstream effector mechanisms of apoptosis, such as activation of caspase-3, is operative, and whether an iron-related oxidative imbalance, occurring inside RBCs and in plasma, could be involved in caspase-3 activation. In 26 patients with type 2 diabetes and in 12 healthy subjects, oxidative stress was evaluated by means of different markers; non-protein-bound iron, methemoglobin and glutathione were determined in RBCs, and non-protein-bound iron was also determined in plasma. Erythrocyte caspase-3 activation was evaluated by an immunosorbent enzyme assay. Arterial hypertension, demographic and standard biochemical data were also evaluated. The results show, for the first time, that type 2 diabetic RBCs put into motion caspase-3 activation, which is significantly higher than in control RBCs. Such an effector mechanism of “eryptosis” was positively correlated to blood glucose levels and to the increased plasma NPBI level. Caspase-3 activation was also positively correlated to occurrence of arterial hypertension. The results suggest that an extracellular oxidative milieu can be responsible for erythrocyte caspase-3 activation in patients with type 2 diabetes. In turn, caspase-3 activation can be envisaged as a novel mechanism which, by impairing the maintenance of erythrocyte shape and function, might contribute to the shortened life span of RBCs from patients with type 2 diabetes and to hemorheological disorders observed in these patients.